Pedagogical Factors İn The Formation Of National-Musical Thinking Of Students İn The Activities Of Music Circles - Zaretdinov Karamatdin Qurbanbaevich (International Journal of Advanced Science and Technology, 2020)
This scientific article deals with the content of modern updated education, and pedagogical factors in solving the current problems of forming students' musical thinking in accordance with its requirements.